Direction and Stability of Hopf Bifurcation in a Delayed Solow Model with Labor Demand - Sanaa ElFadily; Abdelilah Kaddar; Khalid Najib (International Journal of Differential Equations)
This paper is concerned with a delayed model of mutual interactions between the economically active population and the economic growth. The main purpose is to investigate the direction and stability of the bifurcating branch resulting from the increase of delay. By using a second order approximation of the center manifold, we compute the first Lyapunov coefficient for Hopf bifurcation points and we show that the system under consideration can undergo a supercritical or subcritical Hopf bifurcation and the bifurcating periodic solution is stable or unstable in a neighborhood of some bifurcation points, depending on the choice of parameters.